Connecting bioloy, optics and nanomechanical properties in micro-wasps - Mora Castro, Rebeca (2020)
Coloration in insects provides a fruitful opportunity for interdisciplinary research involving both physics and biology, and for a better understanding of the design principles of biological structures. In this research we used nanometric and micrometric analyses to investigate the morphological and mechanical properties of the black-orange-black (BOB) color pattern in scelionid wasps, which has never been studied. The primary objective of the present investigation was to explore the structural and mechanical differences in the mesoscutum of four species: Baryconus with an orange mesosoma (i.e. BOB pattern), all black Baryconus, Scelio with an orange mesosoma (i.e. BOB pattern), and all black Scelio. The most outstanding findings include the absence of multilayer structures that generate structural color, a pigment concentrated in the upper surface of the epicuticle, and surprising differences between the four species. Three of the four species showed an accordion-like structure in the furrow (notaulus), whereas the adjacent mesoscutum was different in each species. Moreover, the normalized color component spectra for blue, green and red colors of the black mesoscutum of each genus showed the same spectral dependence while the orange color manifested small changes in the dominant wavelength, resulting in slightly different orange tones.